Immune checkpoint molecules in prevention and development of asthma - Kanannejad, Zahra; Soleimanian, Saeede; Ghahramani, Zahra; Sepahi, Najmeh; Mohkam, Milad; Alyasin, Soheila; Kheshtchin, Nasim (Frontiers in Immunology, 2023)
Allergic asthma is a respiratory disease initiated by type-2 immune responses characterized by secretion of alarmins, interleukin-4 (IL-4), IL-5, and IL-13, eosinophilic inflammation, and airway hyperresponsiveness (AHR). Immune checkpoints (ICPs) are inhibitory or stimulatory molecules expressed on different immune cells, tumor cells, or other cell types that regulate immune system activation and maintain immune homeostasis. Compelling evidence indicates a key role for ICPs in both the progression and prevention of asthma. There is also evidence of asthma development or exacerbation in some cancer patients receiving ICP therapy. The aim of this review is to provide an updated overview of ICPs and their roles in asthma pathogenesis, and to assess their implications as therapeutic targets in asthma.